2017
DOI: 10.1080/02701960.2017.1287075
|View full text |Cite
|
Sign up to set email alerts
|

Come, join, lead: Attracting students to careers in aging and promoting involvement in gerontological societies

Abstract: Geriatric educators face the challenge of attracting more clinicians, scientists, and educators into geriatrics and gerontology, and promoting involvement in gerontological societies. A survey of psychologists (N = 100) examined factors that attract students in clinical/counseling psychology to practice with older adults, as well as experiences in organizational service. For 58%, interest in aging began at the undergraduate level, but for others interest developed later. About one half cited academic exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 15 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Although a number of papers and internet resources address mentorship programs (5–8), very few focus on development of an academic research career for physician-scientists (3, 912). These resources are mostly institution-based and oriented to students and/or graduate medical trainees (1315). Two recent papers addressed more sponsorship-type programs instead of structural research mentorships (16, 17).…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of papers and internet resources address mentorship programs (5–8), very few focus on development of an academic research career for physician-scientists (3, 912). These resources are mostly institution-based and oriented to students and/or graduate medical trainees (1315). Two recent papers addressed more sponsorship-type programs instead of structural research mentorships (16, 17).…”
Section: Introductionmentioning
confidence: 99%
“…Many were actively engaging these obstacles to enhance attitudes and build academic readiness. Further, some respondents noted a sincere preference for a clinical career and the need to support all career paths through exposure to older populations, a well-documented strategy to enhance interest in aging careers (Cheung et al, 2023; Moye et al, 2018). A six-session career pathway webinar implemented by the Academia work group has tackled some of these issues and continued efforts to address attitudinal barriers and strengthen readiness for academic careers are needed (Harvey et al, 2023; Hill et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…We did not collect demographic information from survey respondents, and therefore cannot discern if any findings were specific to various groups. Our sample was collected using survey methodology similar to that of previous studies of trainees and professionals in clinical geropsychology, in which the overwhelming majority of respondents reported identities as female and non-Hispanic White (Carpenter et al, 2016; Dorman et al, in press; Fiske et al, 2011; Karel et al, 2016; Merz et al, 2017; Moye et al, 2018; Strong, Allen, et al, 2019). Future studies should consider ways in which identity characteristics may influence job attainment, career path, and mentorship needs.…”
Section: Discussionmentioning
confidence: 99%
“…A 2008 survey of mentorship in geropsychology ( N = 29) found that the majority of respondents (89%), ranging from trainees through experienced professionals, reported having at least one mentor and found their mentorship to be very helpful (Fiske, Zimmerman, & Scogin, 2011). Moye et al (2018) surveyed 100 graduates of doctoral and/or postdoctoral programs in geropsychology and found that about half (51%) cited mentorship as a critical factor that drew them into work with older adults. Clearly, mentorship can ensure not only training quality but can also improve the placement, persistence, and success of those working in geriatric mental health.…”
mentioning
confidence: 99%